Endovascular treatment of carotid embolic occlusions has a higher recanalization rate compared with cardioembolic occlusions. (4th December 2009) - Hussain, M S; Lin, R; Cheng-Ching, E; Jovin, T G; Moskowitz, S I; Bain, M; Horowitz, M; Gupta, R
Abstract : Background and purpose: Treatment of large artery cerebral occlusions is rapidly evolving. We hypothesized that patients with intracranial embolic occlusions secondary to an extracranial carotid artery stenosis or occlusion have a higher probability of successful endovascular recanalization compared with those with cardioembolic occlusions. Methods: We retrospectively reviewed the databases of three institutions (University of Pittsburgh Medical Center (UPMC), Michigan State University (MSU) and Cleveland Clinic Foundation (CCF)) for acute anterior circulation ischemic strokes treated with endovascular therapies from January 2006 to July 2008. After collection of demographic, radiographic and angiographic variables, two groups were identified: artery to artery embolic occlusions and cardioembolic/cryptogenic intracranial occlusions. We defined recanalization as TIMI 2 or 3 flow. A binary logistic regression model was constructed to determine which characteristics were unique to patients with carotid embolic occlusions. Results: A total of 207 patients were identified (UPMC=100, CCF=71, MSU=36) with a mean age of 69±11 years and mean NIHSS of 17±5. Of these, 157 (75%) were due to a cardiac or cryptogenic source and 50 (25%) were from a carotid embolic source. The use of multimodal therapy (OR 2.6 (1.2–5.6), p<0.009) and the presence of a carotid embolic intracranial occlusion (OR 3.6 (1.2–7.1), p<0.012) were associated with successful recanalization, while carotid terminus occlusions were associated with unsuccessful recanalization (OR 0.35 (0.18–0.68), p<0.002). Conclusions: Patients with intracranial occlusions secondary to an extracranial carotid stenosis or total occlusion appear to have more successful recanalization rates when treated with endovascular therapy compared with those with cardioembolic occlusions.